The clinical and economic value of the dipeptide alanyl-glutamine in total parenteral nutrition of critically ill patients treated in intensive care units in Italy - Muscaritoli, Maurizio; Pradelli, Lorenzo; Zaniolo, Orietta; Iannazzo, Sergio; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2009)
Introduction: the supplementation of alanyl-glutamine dipeptide in critically ill patients necessitating total parenteral nutrition (TPN) improves clinical outcomes, reducing mortality, infection rate, and shortening ICU hospital lengths of stay (LOS), as compared to standard TPN regimens. Here we present a pharmacoeconomic evaluation of alanyl-glutamine dipeptide in critically ill patients admitted to Italian Intensive Care Units (ICUs). Methods: a Discrete Event Simulation model that incorporates outcomes rates from 200 Italian ICUs for over 60,000 patients, alanyl-glutamine dipeptide efficacy data synthesized by means of a Bayesian Random-Effects meta-analysis, and national cost data has been developed to evaluated the alternatives from the point of view of the hospital. Simulated clinical outcomes are death and infection rates in ICU, death rate in general ward, and hospital LOSs. One-way and probabilistic sensitivity analyses are performed by varying all uncertain parameter values in a plausible range. Results: alanyl-glutamine dipeptide results more effective and less costly than standard TPN: reduced mortality rate (23.55% ± 15.2% vs 34.50% ± 2.06%), infection rate (15.91% ± 3.95% vs 18.97% ± 3.94%), and hospital LOS (25.47 ± 0.26 vs 26.00 ± 0.27 days) come at a lower total cost per patient (23,922 ± 3,249 vs 24,145 ± 3,361 Euro). Treatment cost is completely offset by savings on ICU and antibiotic costs. The cost/effectiveness acceptability curve indicates an estimated 78% probability of alanyl-glutamine dipeptide resulting dominant and a 90% probability of resulting cost/effective for a willingness to pay up to 1,500 Euro for one patient death avoided. Conclusions: alanyl-glutamine dipeptide is expected to improve clinical outcomes and to do so with a concurrent saving for the hospital.